SPECIAL PROTECTION OF EMPLOYEES WITH FAMILY RESPONSIBILITIES AGAINST TERMINATION OF EMPLOYMENT CONTRACT - Balnožan, Kristina (Glasnik Advokatske komore Vojvodine, 2020)
Summary: Loss of employment is one of the most stressful life events for everyone, especially for those with families. An employed mother – and increasingly a father – have family responsabilities towards their children, and these duties are often taken on, due to the family decomposition, by so-called single parents. Family responsabilities towards children are not, however, the only ones: one important segment of the responsabilities of the working age population is the care for elderly and/or sick relatives and/or spouses. In this paper, it will be pointed out that employees with family responsibilities are not a unique legal category. Family responsibilities shall not, as such, constitute a valid reason for termination of employment. The research below, therefore, seeks to show special protection against termination of employment contracts of different categories of employees with obligations to children, and to check whether and in what way such protection is provided to employees with obligations to other family members, since special protection from the termination of the employment contract in the national law explicitly is guaranted to the employees only during pregnancy, absence from work due to special/child care. In this regard, international standards relevant to the subject of research are considered, as well as certain foreign systems that differently take into account the family situation of employees, using primarily normative, comparative law method.